The impact of culture on work attitudes and its implications on managerial roles. - Chua, Mia Wen Shya. (2013)
Managers and management educators worldwide are becoming increasingly aware that management theory and practice need to pay particular attention to the cultural dimension. Our project aims to address the issue of culturally appropriate management strategies with particular attention paid to leadership qualities of a manager. The study is based on the four dimensions (power distance, uncertainty avoidance, individualism and masculinity) devised by Geert Hofstede, a culture guru. The focus is placed in two countries, one in Asia(Singapore) and one in Europe(Sweden).